(untitled) (The Pretoria Student Law Review, 2023)
In recent years there have been reports of the Department of Home Affairs changing women’s surnames to that of their husbands upon the conclusion of a marriage without the married women’s consent. This conduct by the Department of Home Affairs officials infringes, as this article will argue, not only on the affected women’s right to just administrative action but also on the rights to equality and dignity and, in some instances, freedom of movement and universal suffrage. This article enquires into the possibility of taking the conduct of the Department of Home Affairs, which arguably amounts to administrative action, on judicial review seeking systemic relief. It will look at the sexist and patriarchal social norms relied upon to justify the conduct of the Department of Home Affairs and calls for intervening measures that not only result in broader social recognition but also effectively dismantle the systems and frameworks of inequality that continue to marginalise and subjugate women in the socially constructed gender hierarchy.